Serum and Erythrocyte Magnesium levels in Offsprings of Essential Hypertensive Parents (Bangladesh Journal of Medical Biochemistry, 2013)
Hypertension is an important public health challenge worldwide, 95% of which are primary or essential hypertension, where the exact causes are not known. It has been thought that magnesium level has an association with hypertension and plays role in the pathogenesis of essential hypertension. Several evidences suggested that decreased magnesium level may be a significant modifiable risk factor for developing essential hypertension. To explore the relationship between serum and erythrocyte magnesium level with blood pressure, this case control study was carried out in the Department of Biochemistry, Bangabandhu Sheikh Mujib Medical University (BSMMU), during the year 2006. Thirty offsprings of essential hypertensive parents were taken as cases and 30 age and sex-matched offsprings of normotensive parents were taken as controls. Serum & erythrocyte magnesium were measured by colorimetric Calmagite method. Significantly lower serum magnesium level (mg/dl) was found in cases than that of controls (1.90±0.210 vs 2.13±0.366, p